2012
DOI: 10.1111/clr.12052
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines expression in saliva and peri‐implant crevicular fluid of patients with peri‐implant disease

Abstract: Elevated levels of IL-1β in PICF seem to be a characteristic trait of patients with peri-implantitis. The parotid duct saliva showed a significant increase in expression of IL-8, which might be related to a systemic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 27 publications
8
88
1
Order By: Relevance
“…Thirteen studies showed higher levels of IL-1β in PICF than healthy implant sites [7,21,22,30,35,36,41-47]. Of the 10 studies assessed TNF-α, 3 of them showed no relationship with this cytokine with peri-implant inflammation [7,25,43], while other 7 studies showed significant relationship with this cytokine [23,24,36,41,46-48]. These findings suggest that pro-inflammatory cytokines such as IL-1β and TNF-α are up to date, the most promising proteins to be used as markers in PICF for differentiation between peri-implantitis and healthy implants.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies showed higher levels of IL-1β in PICF than healthy implant sites [7,21,22,30,35,36,41-47]. Of the 10 studies assessed TNF-α, 3 of them showed no relationship with this cytokine with peri-implant inflammation [7,25,43], while other 7 studies showed significant relationship with this cytokine [23,24,36,41,46-48]. These findings suggest that pro-inflammatory cytokines such as IL-1β and TNF-α are up to date, the most promising proteins to be used as markers in PICF for differentiation between peri-implantitis and healthy implants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a variety of inflammatory biomarkers (e.g., IL-1β, IL-6, and immunoglobulins) are present in the UWS of patients with oral and systemic disorders [17][18][19]. Therefore, the noninvasive assessment of UWS may yield valuable information and can be used to monitor the severity of oral inflammatory conditions, including peri-implantitis [17,20]. IL-1β and IL-6 are the most common inflammatory cytokines that enhance bone resorption by increasing osteoclastic activity [18].…”
Section: Introductionmentioning
confidence: 99%
“…More recently multiplex cytokine arrays have been applied in the analysis of PICF, allowing for a broader simultaneous screening of multiple inflammatory cytokines and chemokines. In one such study, 12 markers were assessed in both peri-implant health and disease, including granulocyte macrophage colony-stimulating factor (GM-CSF), IL-1β, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12, interferon (IFN)-γ and TNF-α (Fonseca et al 2014). In line with previous findings, there were no differences with regards to IL-6, IL-8, IL-10 (Severino et al 2011), whereas the levels of IL-1β were significantly higher at peri-implantitis, compared to mucositis sites.…”
mentioning
confidence: 99%